Asssociate rull using heldge algebra approach - Sơn, Trần Thái; Tiến, Đỗ Nam; Phong, Phạm Đình (Journal of Computer Science and Cybernetics, 2012)
In this paper we introduce the new method to quantitative association rule mining from relational data base using Hedge Algebras approach. This approach let transform values in DB into fuzzy values in more natural way and reduce a volume of computational information.